Fiscal stability of local budgets in the context of administration of excise tax from retail of tobacco articles - N.V. Bakhur (Економіка, управління та адміністрування)
The excise tax from retail of tobacco articles takes an important place among additional tax proceeds of societies. This tax allows to fill up the profitable part of local budgets fast and may be directed to the needs of societies. The important component of country’s budgetary system are local budgets. The cause of disbalance in the budgetary system may be the change in the conditions of formation and fulfilment of local budgets. The financial basis for of local budgets are profits. The fair distribution of resources among the budgets of local government has to be provided. It is very significant to increase the tax culture of taxpayers. The present factor also influences filling up local budgets. It is also necessary to avoid the illegal circulation of excisable goods and help controlling bodies timely disclose such facts. To increase the amounts of receipts to local budgets and ensure the competitive environment for tobacco market it is necessary to improve the administration of excise tax from retail of tobacco articles. The author analyzes the impact of excise tax from retail of tobacco articles on the formation of the profitable part of local budgets and the situation with its possible cancellation. The paper proposes the recommendations about the improvement of conditions in the administration of excise tax from retail of tobacco articles, and also the ways of prevention from illegal selling these products to provide the control for timely payment of this tax: to improve the payment order of the excise tax from retail of tobacco articles to local budgets, to take measures concerning the introduction of the automated system «Electronic excise mark», to accept the measures on implementing the Strategy directed to the counteraction of illegal production and circulation of tobacco articles till 2021.